Longitudinal displacement in viscoelastic arteries:A novel fluid-structure interaction computational model, and experimental validation - Martina Bukač; Sunčica Čanić (Mathematical Biosciences and Engineering)
Recent in vivo studies, utilizing ultrasound contour and speckle tracking methods, have identified significant longitudinal displacementsof the intima-media complex, and viscoelastic arterial wall properties over a cardiac cycle. Existing computational models that use thin structure approximations of arterial walls have so far been limited to models that capture only radial wall displacements.The purpose of this work is to present a simple fluid-struture interaction (FSI) model and a stable, partitioned numerical scheme, which capture both longitudinal and radial displacements,as well as viscoelastic arterial wall properties.To test the computational model,longitudinal displacement of the common carotid artery and of the stenosed coronary arteries were compared with experimental datafound in literature, showingexcellent agreement. We found that, unlike radial displacement, longitudinal displacement in stenotic lesionsis highly dependent on the stenotic geometry.We also showed that longitudinal displacement in atherosclerotic arteries is smaller than in healthy arteries,which is in line with the recent in vivo measurements that associate plaque burden with reduced total longitudinal wall displacement.    This work presents a first step in understanding the role of longitudinal displacement in physiology and pathophysiology of arterial wall mechanicsusing computer simulations.